Venovenous Extracorporeal Membrane Oxygenation as a Treatment for Obesity Hypoventilation Syndrome - Nao Umei; Shingo Ichiba (Case Reports in Critical Care)
The mortality rate for respiratory failure resulting from obesity hypoventilation syndrome is high if it requires ventilator management. We describe a case of severe acute respiratory failure resulting from obesity hypoventilation syndrome (BMI, 60.2 kg/m2) successfully treated with venovenous extracorporeal membrane oxygenation (VV-ECMO). During ECMO management, a mucus plug was removed by bronchoscopy daily and 18 L of water was removed using diuretics, resulting in weight loss of 24 kg. The patient was weaned from ECMO on day 5, extubated on day 16, and discharged on day 21. The fundamental treatment for obesity hypoventilation syndrome in morbidly obese patients is weight loss. VV-ECMO can be used for respiratory support until weight loss has been achieved.